Compliance Analysis of the Implementation of the Public Accountant Professional Code of Ethics by Public Accountants in Indonesia - Angelina Chang; Stefy Stefy; Winny Winny (LAFADZ JAYA Publisher, 2022)
This study aims to analyze the application of the code of ethics for the public accounting profession in Indonesia. The research method used in this research is to use qualitative methods, in which researchers collect data from various references to scientific works, articles, journals and other references. While the data collection technique that the authors use is to use the literature study technique. The object of this research is a public accountant in the Indonesian Public Accounting Firm. The results of this study conclude that the application of a code of ethics for the public accounting profession is very important to guarantee public trust. In addition, by applying a code of ethics, an accountant is seen as more professional, reliable and trustworthy. An accountant must be independent because a lack of independence can violate the basic principles of ethics regarding the objectivity of an auditor at work.